Thermal dependence of the strain response of optical fibre Bragg gratings. - O'Dwyer, Martin; Ye, Chen-Chun; James, Stephen W.; Tatam, Ralph P. (IOP Publishing, 2004)
The temperature dependence of the strain sensitivity of fibre Bragg gratings written into a number of different fibre types has been investigated. It was found that the strain response changed on average by 0.21 ± 0.03 fm µε-1 °C-1 over a range of temperatures between 100–400 °C. These results were in agreement with predictions based on material parameters.
Keywords: Bragg gratings; strain response; temperature dependence